Design and assessment of a core-power controller for lithium-cooled space nuclear reactor based on the concept of fuzzy model predictive control - Yin, Yuan; Yuan, Zhenheng; Pang, Bo; Xiao, Yiqing; Deng, Yangbin (Frontiers in Energy Research, 2023)
Thanks to its unique characteristics of high power-to-mass ratio, shallow reactivity poisoning, and quick response to reactivity control, power supply system based on lithium-cooled space nuclear reactor is preferred for various exploration missions into outer and deep space. However, due to its nature of few-people or even unmanned on-duty, an intelligent autonomous control of the reactor system, especially an accurate control of the reactor core power following the demanding power output, is of vital importance for such a space nuclear reactor. In this study, a fuzzy model predictive controller (FMPC) for the core-power control of a megawatt ultra-small lithium-cooled space nuclear reactor was designed based on the combined concept of model predictive control and T-S fuzzy theory. Performance of the FMPC controller was simulated and assessed with the Simulink platform for five typical operation transients including ramp, step and disturbance transient. The results show that the intelligent FMPC controller possesses an excellent load-following ability and anti-interference ability, both of which are of vital importance for space exploration missions. When compared with the classical PID controller, the FMPC controller designed in this study shows also a much better performance with smaller overshoot, lesser adjusting time and lower integral time-squared error.